2020
DOI: 10.1016/j.chemosphere.2020.127000
|View full text |Cite
|
Sign up to set email alerts
|

Developmental programming: Transcriptional regulation of visceral and subcutaneous adipose by prenatal bisphenol-A in female sheep

Abstract: Background: Bisphenol-A (BPA) exposure is widespread and early life exposure is associated with metabolic syndrome. While visceral adipose tissue (VAT) and subcutaneous adipose tissue (SAT) are implicated in the development of metabolic syndrome, the adipose depot-specific effects of prenatal BPA treatment are poorly understood.Objective: To determine the impact of prenatal BPA exposure on the transcriptome of VAT and SAT adipose depots. Methods: RNA sequencing was performed on SAT and VAT from 21-month old co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 111 publications
0
1
0
Order By: Relevance
“…However, other studies showed different results regarding the behavior of subcutaneous adipose tissue in the presence of BPA. Another study, evaluating sheep exposed to BPA with daily doses of 0.5 mg/kg during their fetal growth, demonstrated development of visceral adipose tissue hypertrophy at 21 months after birth [81]. This treatment allowed free BPA concentrations of 2.62 ± 0.52 ng/mL collected from the umbilical artery on day 90 of fetal life with values within the range observed in human umbilical cord blood concentrations at mid-gestation [27].…”
Section: Experiments In Fetal Programming: Effect Of Bpa On Adipose T...mentioning
confidence: 81%
See 1 more Smart Citation
“…However, other studies showed different results regarding the behavior of subcutaneous adipose tissue in the presence of BPA. Another study, evaluating sheep exposed to BPA with daily doses of 0.5 mg/kg during their fetal growth, demonstrated development of visceral adipose tissue hypertrophy at 21 months after birth [81]. This treatment allowed free BPA concentrations of 2.62 ± 0.52 ng/mL collected from the umbilical artery on day 90 of fetal life with values within the range observed in human umbilical cord blood concentrations at mid-gestation [27].…”
Section: Experiments In Fetal Programming: Effect Of Bpa On Adipose T...mentioning
confidence: 81%
“…In addition, differential gene expression was evaluated by tissue type (subcutaneous vs. visceral) and by treatment (control vs. prenatal BPA group). The results showed, when tissue type was compared, a positive regulation of inflammation, oxidative stress, and adipose differentiation genes in subcutaneous adipose tissue compared to in visceral adipose tissue [81]. However, when comparing subcutaneous tissue gene expression for each treatment (control vs. BPA treatment), BPA downregulated several genes involved in immune cell pathways, including those involved in leukocyte activation, inflammatory response, and cytokine production.…”
Section: Experiments In Fetal Programming: Effect Of Bpa On Adipose T...mentioning
confidence: 96%
“…Visceral adipose tissue (VAT) and subcutaneous adipose tissue (SAT) are the two major types of adipose tissue, according to their distribution in mammals [4]. There are many differences between VAT and SAT including anatomical, cellular, molecular, physiological, clinical, and prognostic [5]. Fat storage and allocation within body depots of farm animals are associated with animal health and meat quality, these differences are caused by a variety of mechanisms such as a different content of immune cells, different sensitivity to lipolytic and antilipolytic stimulation, and different metabolic activities [6] [7].…”
Section: Introductionmentioning
confidence: 99%